Subjective well-being in China: The role of relative income, gender and location - Asadullah, M.N.; Xiao, S. (2015)
We use data from two rounds of Chinese General Social Survey (CGSS) to study the determinants of subjective well-being in China over the period 2005-2010 during which self-reported happiness scores show an increase across all income groups. Ordered probit regression of well-being function reveals large influence of gender, rural residency and household income. Net of control for demographic attributes, health, employment and education status, household assets, the influence of past and future income and province dummies, we find that women, urban resident and people with higher income are happier in China. More schooling and better health are positively and significantly correlated with well-being. Sub-sample analysis reveals that the rich only cares about the relative income whereas the effect of absolute income dominates in case of the poorer section. At the same time, we find significant relative income effect in determining well-being among the poor. The influence of absolute income is larger among female (rural residents) causing a happiness gap vis-à-vis males (urban residents) in the conditional (unconditional) distribution of happiness. Our results suggest that while further growth in private income and reduction in rural poverty will enhance well-being in China, policies that reduce inequality are likely to boost well-being in both rural and urban locations.